Emerging multinationals: globalisation paths and management styles - (:unkn) unknown (INDERSCIENCE ENTERPRISES LTD, 2012)
Recent years have seen the appearance of a growing number of MNCs from emerging economies. Whereas these firms have essentially had humble beginnings, some of them have become global leaders over the years. Despite the interest in the topic of emerging multinationals as such, only recently a growing strand of literature has begun to question the phenomenon. The literature on emerging multinationals is now rapidly growing but is still in its infancy and has not yet reached any definite conclusions. In this thematic issue, we address the subject by presenting six papers, which tackle complex and important managerial matters related to emerging multinationals from different parts of the world.
Keywords: multinational companies; globalisation; emerging markets; ECONOMIES